Clinical And Functional Outcome Between All Arthroscopic Vs. Mini-Open Surgery in Rotator Cuff Injury: A Meta-Analysis - Stedy Adnyana Christian; Shianita Limena (Indonesian Journal of Global Health Research, 2023)
Rotator cuff tear portrays a frustrating experience with shoulder dysfunction and disability. Surgical repair showed satisfactory results when conservative treatment failed or not-indicated. Along with the surgical advancement, mini-open and arthroscopic surgery have a growing preference with minimal scarring, desirable pain relief, and functional improvement. To date, there are inconclusive results on which type of surgery is superior. Functional outcome and complication rates are equally balanced between the two surgeries, while some studies favor arthroscopic repair. The aim of study is to compare the clinical and functional outcome between arthroscopy and mini-open surgery for rotator cuff repair according to recent publications. This study conducted a thorough search for relevant scientific reports on multiple medical databases, including PubMed, Embase, and Google Scholar, using a combination of keywords such as "arthroscopic surgery," "mini-open surgery," and "rotator cuff repair". The search was performed in March 2013-2023, resulted in 576 studies. Two reviewers (SA, SL) independently screened the abstracts and reference lists, with any discrepancies resolved through consensus, concluding 3 included studies. The review aimed to answer the research question by comparing the clinical and functional improvements achieved with each treatment option. Three studies included studies are included with a total 469 patients consisting of 235 patients undergoing all arthroscopic and 234 patients undergoing mini-open rotator cuff repair. At 24 months follow-up, there are similar satisfactorily significant clinical and functional outcomes, including VAS score, range of motion, DASH and Constants score. Arthroscopic and mini-open surgeries serve equally balanced excellent options for rotator cuff repairs, providing pain relief, restoration of ROM, and improved functional outcomes.